Dynamics of relative area of rat liver structures in early postnatal period in norm and after intrauterine effect of an antigen or glucocorticoids. - M. A. Voloshin; P. V. Bohdanov (Морфологія, 2016)
Background. Infectious diseases that can exacerbate normal pregnancy affect not only maternal health, but also the future baby. Most infectious agents, primarily TORCH-infections and of bacterial ones, are tropic to liver and biliary ductules epithelium and can be the reason of congenital hepatitis and defects.